A triptycene-based two-dimensional porous organic polymeric nanosheet. Issue 36 (16th August 2017) - Chen, Jing-Jing; Zhai, Tian-Long; Chen, Yi-Fan; Geng, Shinan; Yu, Chan; Liu, Jun-Min; Wang, Linling; Tan, Bien; Zhang, Chun
Abstract : A new application of the "old" Glaser coupling reaction for a two-dimensional porous polymeric nanosheet on an air/liquid interface is developed. Abstract : The greater structural versatility of two-dimensional polymeric nanosheets could be available through the development of a bottom-up polymerization strategy compared with top-down nanosheets (such as graphene and metal chalcogenides). However, rational synthesis by solution polymerization has been a long-standing challenge. Considering that Glaser coupling is catalyzed by cuprous (I) salts with the participation of oxygen, an air/liquid interfacial coupling reaction has been designed and used to prepare a two-dimensional porous triptycene-based polymeric nanosheet (2D-PTNS ). This2D-PTNS shows a high BET surface area, good gas adsorption ability and excellent selective adsorption of C2 H6 /CH4 at ambient temperature and pressure.